2021
DOI: 10.4025/actasciagron.v44i1.53213
|View full text |Cite
|
Sign up to set email alerts
|

Detection and transmission of Fusarium verticillioides in corn seeds according to the plant stage

Abstract: The objective of this study was to evaluate the transmissibility of F. verticillioides, in corn seeds, when inoculated in different phenological stages. The plants were inoculated with the pathogen at the following stages: V7, V9, R1, R2, R4, and R6. The experiments were conducted in pots, in a completely randomized design, with six replications. The fungus infection rate in the seeds was verified through the health test (Blotter Test). The significance of the contrast between the phenological stages and in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Inconsistent pathogenic behaviour according to the host growth stage has also been found in other studies. For example, in tissues infected by F. verticillioides , only the infections occurring at seedling and young plant stages of maize showed high radicle decay ability (Venturini et al, 2013), although Sousa et al (2021) recently found that in the reproductive phenological stages, the plant was more susceptible to the infection of the same pathogen. Infections of F. oxysporum at the early seedling growth stage of Lupinus luteus showed that the disease was particularly aggressive after the change from autotrophic to heterotrophic phase of the plant, that is, up to 72 h of growth (Morkunas et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent pathogenic behaviour according to the host growth stage has also been found in other studies. For example, in tissues infected by F. verticillioides , only the infections occurring at seedling and young plant stages of maize showed high radicle decay ability (Venturini et al, 2013), although Sousa et al (2021) recently found that in the reproductive phenological stages, the plant was more susceptible to the infection of the same pathogen. Infections of F. oxysporum at the early seedling growth stage of Lupinus luteus showed that the disease was particularly aggressive after the change from autotrophic to heterotrophic phase of the plant, that is, up to 72 h of growth (Morkunas et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These containers were then placed in an incubation chamber (BOD) under a 12 h photoperiod, maintaining a temperature of 25 ± 2 • C for 24 h. Following this incubation, the containers were transferred to a freezer at −20 • C for 24 h to inhibit seed germination. Subsequently, they were returned to the incubation chamber at 25 ± 2 • C, under a 12 h photoperiod, for five days for the growth of fungi [21]. Following established literature guidelines, pathogens were identified by examining their morphological characteristics under magnification [20].…”
Section: Evaluation Of Losses Of Flowers Pods and Grainsmentioning
confidence: 99%
“…Nirenberg were the most predominant species reported in agriculture fields in Germany and New Zealand ( Hussein et al., 2003 ; Görtz et al., 2008 ). Fv has also been detected in Brazil ( de Sousa et al., 2022 ), China ( Qiu et al., 2015 ), France ( Atanasova-Penichon et al., 2014 ), and Mexico ( Leyva-Madrigal et al., 2015 ). Mexico has high maize yield losses from Fusarium rot ( González Huerta et al., 2007 ; Briones-Reyes et al., 2015 ; Lizárraga-Sánchez et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%